Analysis o leadership style and motivation on turnover intention mediated by employee loyalty at PT. WOM finance - Rina Mayangsari; Adrie Frans Assa (Enrichment : Journal of Management, 2026)
This study aims to examine the Effect of Competence, Work Motivation, and Workload on Employee Performance with Job Satisfaction as a Mediating Variable for Operations Employees at PT. WOM Finance. The study used a quantitative approach with 268 customer respondents. Data analysis was performed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of the SmartPLS 4 application. These three variables are ultimately closely related to employee psychological well-being, one of which is job satisfaction. Consequently, numerous studies have shown that competence, work motivation, and workload not only directly influence performance but are also influenced by job satisfaction as a mediator. Employees who feel satisfied with their work tend to have positive energy and make a greater contribution to the company. The results showed that Work Competence (X1) had a positive and significant effect on Job Satisfaction (Z) with a coefficient of 0.151 and a p-value of 0.001 (<0.05). Work competence also has a positive and significant effect on Employee Performance (Y) with a coefficient value of 0.436 and a p-value of 0.000 (<0.05). The Work Motivation variable (X2) has a positive and significant effect on Job Satisfaction (Z) with a coefficient value of 0.516 and a p-value of 0.000 (<0.05). In addition, Work Motivation also has a positive and significant effect on Employee Performance (Y) with a coefficient value of 0.270 and a p-value of 0.000 (<0.05). Furthermore, Workload (X3) has a negative and insignificant effect on Job Satisfaction (Z) with a coefficient value of -0.132 and a p-value of 0.000 (<0.05). The Job Satisfaction variable (Z) has a positive and significant effect on Employee Performance (Y) with a coefficient value of 0.208 and a p-value of 0.000 (<0.05). Job Competence (X1) has an indirect influence on Employee Performance (Y) through Job Satisfaction (Z) with a coefficient value of 0.031, a T Statistics value of 2.534, and a p-value of 0.011 (<0.05). These results indicate that Job Satisfaction is able to significantly mediate the influence of Job Competence on Employee Performance. Work Motivation (X2) also has an indirect influence on Employee Performance (Y) through Job Satisfaction (Z) with a coefficient value of 0.107, a T Statistics value of 3.906, and a p-value of 0.000 (<0.05). These results indicate that Job Satisfaction is able to significantly mediate the influence of Work Motivation on Employee Performance. Furthermore, Workload (X3) has an indirect effect on Employee Performance (Y) through Job Satisfaction (Z), with a coefficient value of -0.028, a T-statistic of 3.235, and a p-value of 0.001 (<0.05).